PENGARUH MEDIA PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR KOGNITIF DAN PSIKOMOTORIK IPA SISWA KELAS IV SD NEGERI 01 KANDANGMAS - Muhammad Arifin (Jurnal Guru Kita PGSD, 2018)
Abstract: The Effect of Media Mind mapping on the Cognitive and Psychomotor Learning Outcomes of Students in Grade IV of SD Negeri 01 Kandangmas. This study aims to determine and analyze the effect of Mind mapping media on cognitive and psychomotor learning outcomes of the fourth grade students of SD Negeri 01 Kandangmas. This study uses True Experimental Design in the form of Pretest-Posttest Control Group Design. The population in this study were all fourth grade students of SD Negeri 01 Kandangmas who were still active as students in the school during this research. The results showed the results of the final analysis that had been carried out using the band test because thitung> t table was 4.47771> 2.1009 meaning that Ha was accepted. because thitung> t table is 4.47771> 2.1009 means that Ha is accepted, so it can be concluded that there is influence of Mind mapping media on cognitive and psychomotor learning outcomes of the science of fourth grade students of SD Negeri 01 Kandangmas.Keyword : Mind mapping Media, Cognitive and Psychomotor Learning Outcomes.Abstrak : Pengaruh Media Mind mapping Terhadap Hasil Belajar Kognitif dan Psikomotorik IPA Siswa Kelas IV SD Negeri 01 Kandangmas. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh media Mind mapping terhadap hasil belajar kognitif dan psikomotorik IPA siswa kelas IV SD Negeri 01 Kandangmas. Penelitian ini menggunakan True Experimental Design bentuk Pretest-Posttest Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas IV SD Negeri 01 Kandangmas yang masih tercatat aktif sebagai siswa di sekolah selama penelitian ini dilakukan. Hasil penelitian menunjukkan hasil analisis akhir yang telah dilakukan dengan menggunakan uji bandingkarena thitung > ttabel yaitu 4,47771 > 2,1009 artinya Ha diterima. karena thitung > ttabel yaitu 4,47771 > 2,1009 artinya Ha diterima, sehingga dapat disimpulkan bahwa ada pengaruh media Mind mapping terhadap hasil belajar kognitif dan psikomotorik IPA siswa kelas IV SD Negeri 01 Kandangmas.Kata Kunci : Media Mind mapping, Hasil belajar Kognitif dan Psikomotorik IPA.